Pengujian Eksperimental Model Sambungan Balok-Kolom Beton Pracetak - Kharisma Nur Cahyani (Jurnal Serambi Engineering, 2023)
The main issue in the implementation of precast concrete systems lies in the connections. The connections in precast systems must possess the strength to withstand the occurring loads. One of the methods used for connecting precast concrete is the dry connection method. To test the connections of precast beam-columns, a quasi-cyclic loading test is utilized, which generates data on the relationship between load (P) and displacement (∆). The test results indicate that test specimens using 4 anchors have a higher maximum capacity compared to those using 2 anchors. Additionally, the cycles that occur in the test specimen with 2 anchors are longer than those in the specimens with 4 anchors and monolithic specimens. The peak load is achieved by the test specimen with 4 anchors, reaching 1488 kg at a displacement of 18 mm, specifically at a 2% drift. Both the monolithic and 4-anchor test specimens have the same drift, reaching 2%. However, the longest cycles occur in the test specimens with 2 anchors, reaching a 4% drift. Consequently, it can be concluded that the test specimens with 4 anchors have a greater capacity and shorter cycles compared to those using 2 anchors and the monolithic specimens.